The Story of a Seagull and the Cat Who Taught Her to Fly - Luis Sepulveda (Surrey, United Kingdom Alma Books Ltd, 2016)
A Cat, A Seagull, An Impossible Task...Caught up in an oil spill, a dying seagull scrambles ashore to lay her final egg and lands on a balcony, where she meets Zorba, a big black cat from the port of Hamburg. The cat promises the seagull to look after the egg, not to eat the chick once it's hatched and - most difficult of all - to teach the baby gull to fly. Will Zorba and his feline friends honour the promise and give Lucky, the adopted little seagull, the strength to discover her true nature?A moving, uplifting and life-enhancing story with a strong environmental theme, Luis Sepulveda's instant children's classic has been a worldwide best-seller and is presented here with new drawings by acclaimed illustrator Satoshi Kitamura.
Keywords: Fantasy -- Fantasy